PENGARUH DIGITAL SKILL, DIGITAL COLLABORATION, DIGITAL INNOVATIVENESS TERHADAP DIGITAL LEADERSHIP PADA GEN-Z DI SURABAYA - Felicia Juliani Leliga; Oliandes Sondakh (Faculty of Economics and Business Universitas Pelita Harapan, 2026)
The development of digital technology has driven changes in how individuals collaborate, innovate, and lead in various contexts, including academic settings. Therefore, understanding the factors influencing digital leadership skills is crucial to supporting the younger generation's readiness for the era of digital transformation. This study aims to analyze the influence of Digital Skill, Digital Collaboration, and Digital Innovativeness on Digital Leadership in students. This study used a quantitative approach with a survey method. The population in this study were active students, while the research sample consisted of 99 respondents selected using a purposive sampling technique. Data was collected through a questionnaire measured using a five-level Likert scale. Data analysis was performed using multiple linear regression analysis with the help of SPSS software. Before conducting the regression analysis, the data were first tested through validity and reliability tests, as well as classical assumption tests including normality, multicollinearity, heteroscedasticity, and linearity tests. The results showed that DS, DC, and DI had a positive and significant influence on DL. Among the three variables, DC had the most dominant influence on DL. The results of this study indicate that improvements in DS, DC, and DI aspects can support the improvement of DL. Therefore, developing digital competencies, strengthening collaboration, and increasing innovation are important factors in supporting the effectiveness of DL in the academic environment.